Lethal suicide attempt with a mixed-drug intoxication of metoprolol and propafenone - A first pediatric case report - Kacirova, Ivana; Grundmann, Milan; Kolek, Martin; Vyskocilova-Hrudikova, Erika; Urinovska, Romana; Handlos, Petr (Forensic science international, 2017)
INTRODUCTION: The β1 adrenergic receptor blocker metoprolol is often prescribed together with the antiarrhythmic drug propafenone. Both are metabolized by cytochrome P450 2D6 and propafenone is also an inhibitor of this enzyme. We present a pediatric case showing metoprolol and propafenone intoxication in combination. CASE: A 14-year-old girl was admitted to a local emergency department after ingestion of metoprolol (probably 1g) and propafenone (probably 1.5-3g) in a suicide attempt. She developed cardiogenic shock with cardiac arrest and was fully resuscitated. Veno-arterial femorofemoral extracorporeal membrane oxygenation was started immediately. High serum levels of both drugs were detected approximately 10h after ingestion (2630ng/mL metoprolol and 2500ng/mL propafenone). Other serial samples for the monitoring of the levels of metoprolol and its metabolite alfa-hydroxymetoprolol were obtained between days 2 and 4 after admission. The metoprolol/alfa-hydroxymetoprolol ratio on the 2nd day was 36.1, indicative of a poor metabolizer phenotype. The elimination half-life of metoprolol was prolonged to 13.2h and the clearance decreased by about 70%. The patient condition gradually worsened, brain edema and intracerebral hemorrhage occurred, and on the 6th day, the patient died. CONCLUSION: We document a pediatric case report of death due to a mixed drug overdose of metoprolol and propafenone, along with data regarding serum metoprolol, alfa-hydroxymetoprolol, and propafenone levels.
Keywords: antagonisté beta-1-adrenergních receptorů; metoprolol; Phenotyping; antiarytmika; lékové interakce; Intoxication; Anti-Arrhythmia Agents; srdeční zástava; předávkování léky; Drug Interactions; Humans; Shock, Cardiogenic; cerebrální krvácení; Cerebral Hemorrhage; edém mozku; Female; propafenon; mladiství; Adrenergic beta-1 Receptor Antagonists; Heart Arrest; kardiogenní šok; ženské pohlaví; Drug Overdose; sebevražda; Brugada-sign; Adolescent; lidé; Brain Edema; Metoprolol; Suicide; Propafenone